Upaya Penggunaan Model Pembelajaran Jarak Jauh Untuk Meningkatkan Aspek Spiritual Siswa SD 2 Medini - Ervi Rosmayanti (Al Hikmah: Journal of Education, 2020)
In the era of the Covid-19 virus pandemic, all educational services are expected to be taught at home. To overcome this problem, the teacher is anticipating online learning, using a distance learning model. So that students at home can still study. This study aims to determine the efforts to use distance learning models to improve the spiritual aspects of SD 2 Medini students amid the Covid-19 pandemic. This research method uses qualitative methods with the subjects of this study, namely students of class VI SD 2 Medini, Kudus. The results of this study were the implementation of the class VI distance learning model at SD 2 Medini using the WhatsApp application. The obstacles experienced include a commitment from parents and students and students are not consistent with their lesson schedules. Spiritual aspects of distance learning that can be applied in SD 2 Medini include appreciating and living up to the religious teachings that are adhered to. Praying before and after doing something and carrying out worship on timePada era pandemi virus covid-19 ini, semua layanan pendidikan diharapkan belajarkan dirumah. Untuk mengatasi hal tersebut maka guru mensiasati belajar online, dengan menggunakan model pembelajaran jarak jauh. Agar siswa dirumah tetap bisa belajar. Penelitian ini bertujuan untuk mengetahui upaya penggunaan model pembelajaran jarak jauh untuk meningkatkan aspek spiritual siswa SD 2 medini ditengah pandemi covid-19. Metode penelitian ini menggunakan metode kualitatif dengan subyek penelitian ini yaitu siswa kelas VI SD 2 Medini, Kudus. Hasil penelitian ini yaitu pelaksanaan model pembelajaran jarak jauh kelas VI di SD 2 Medini menggunakan aplikasi whatsApp. Hambatan yang dialami diantaranya komitmen dari orang tua dan siswa itu dan siswa tidak konsisten terhadap jadwal pelajarannya. Aspek spiritual dalam pembelajaran jarak jauh yang dapat diterapkan di SD 2 Medini diantaranya menghargai dan menghayati ajaran agama yang dianut Berdoa sebelum dan sesudah menjalankan sesuatu dan Menjalankan ibadah tepat waktu.